The originis of a library and an art collection: letters by Antoine Morillon (around 1520–1556) and Stephanus Pighius (1520–1604) to Antoine Perrenot de Granvelle in Madrid - Wrede, Henning (AVISOS. Noticias de la Real Biblioteca, 2014)
Altogether the correspondence of Antoine Perrenot, bishop of Arras, Cardinal de Granvelle, minister of Charles V and Philipp II, viceroy of Naples and Sicily is extensive. A large part of it is still kept in Madrid. Here we will focus on just 19 letters written to Perrenot by Antoine Morillon (17) and Stephanus Pighius (2). They are located in the manuscripts II/2253, II/2297, II/2298 of the Real Biblioteca and in 20212 of the Biblioteca Nacional. They provide a sense of Perrenot as a rather young bishop prior to establishing his later well-known library and art collection. In the 16th century Stephanus Pighius was a particularly famous antiquarian scholar of Roman history. His native city Kampen in the Netherlands still celebrates him among its outstanding sons